The effect of levomepromazine on the healthy and injured developing mouse brain – An in vitro and in vivo study. (December 2020) - Posod, Anna; Winkler, Ira; Wegleiter, Karina; Huber, Eva; Urbanek, Martina; Kiechl-Kohlendorfer, Ursula; Griesmaier, Elke
Highlights: Levomepromazine (LMP) does not induce cell death in the healthy developing brain. Excitotoxic lesion size and apoptosis are unaffected by LMP. Body weight gain is reduced in mouse pups receiving higher-dose LMP treatment. Further studies are required prior to a routine use of LMP in neonates. Abstract: Levomepromazine (LMP) is a phenothiazine neuroleptic drug with strong analgesic and sedative properties that is increasingly used off-label in pediatrics and is being discussed as an adjunct therapy in neonatal intensive care. Basic research points towards neuroprotective potential of phenothiazines, but LMP's effect on the developing brain is currently unknown. The aim of the present study was to assess LMP as a pharmacologic strategy in established neonatal in vitro and in vivo models of the healthy and injured developing mouse brain. In vitro, HT-22 cells kept exposure-naïve or injured by glutamate were pre-treated with vehicle or increasing doses of LMP and cell viability was determined. In vivo, LMP's effects were first assessed in 5-day-old healthy, uninjured CD-1 mouse pups receiving a single intraperitoneal injection of vehicle or different dosages of LMP. In a second step, mouse pups were subjected to excitotoxic brain injury and subsequently treated with vehicle or LMP. Endpoints included somatometric data as well as histological and immunohistochemical analyses. In vitro, cell viability in exposure-naïve cells was significantly reduced by high doses of LMP, but remained unaffected in glutamate-injured cells. In vivo, no specific toxic effects of LMP were observed neither in healthy mouse pups nor in experimental animals subjected to excitotoxic injury, but body weight gain was significantly lower following higher-dose LMP treatment. Also, LMP failed to produce a neuroprotective effect in the injured developing brain. Additional studies are required prior to a routine clinical use of LMP in neonatal intensive care units.